MODEL FOR IMPLEMENTING SKILLS TRAINING FOR PRE-RETIREMENT MEMBERS OF THE METRO JAYA POLICE - Yustinus Caturiono*; Bambang Giyanto, R.N; Afsdy Saksono (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
This study analyzes the skills training model for National Police members nearing retirement at Metro Jaya Police. The transition to retirement requires adequate skills preparation for smooth adaptation. Using qualitative methods, the study evaluates the training structure, curriculum, and implementation. Data was collected through interviews with trainees, instructors, and officials, as well as direct observations. The findings show that the training model includes various skill modules relevant to the needs of retiring police members. Strengths include material relevance and practical support, while challenges lie in adjusting the curriculum and methodology. The study recommends enhancing these aspects and adding market-oriented skills and psychological support to improve program effectiveness, contributing to a more optimal training model for retiring National Police members..Keywords: Skills Training, Members of the National Police, Retirement, Polda Metro Jaya